ASSESSMENT OF ECOLOGICAL DANGER OF SEEPAGE WATER SOLID WASTE LANDFILL OF KOKSHETAU: ASSESSMENT OF ECOLOGICAL DANGER OF SEEPAGE WATER SOLID WASTE LANDFILL OF KOKSHETAU (Eurasian Journal of Ecology, 2022)
The impact of landfills on the environment is not limited to the dumping of garbage, since the pos-sible penetration of leakage through the subsoil can lead to contamination of groundwater. The study (2021) presents the results of studying the elemental composition of filtration waters and soil of the solid waste landfill in Kokshetau, the period of operation of which at the time of the study was 50 years.Analysis of filtrate samples obtained from landfills showed that the filtrate is a highly concentrated solution containing toxic components. The chemical composition of the filtrate, developed by a gener-ally accepted method from surface aggregation, showed a high content of organic matter and a BOC5 / COC ratio of about 0.01-0.005, which indicates a high content of bioresistant components. It is a liquid from black to yellow-brown in color with a specific odor and a slightly alkaline reaction of the medium (pH = 7.5-8.25). The concentration of heavy metals does not exceed the maximum permissible con-centration for water. The pH value, ammonia ions, high mineralization and concentration of chloride ions are the characteristics of the garbage filter at the operational stage. Normalization of soil quality by chemical indicators showed that at sampling points at a distance of 500 and 1000 m from the landfill corresponds to a dangerous level of pollution, and at a greater distance decreases, these soils belong to the second level of pollution. According to the composition of the filtrate, the landfill belongs to the old landfills.Key words: municipal solid waste, filtration water, environmental impact, pollutants, toxic sub-stances.